2021
DOI: 10.3390/polym13183102
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Bioactive Polymeric Surfaces by Radiation Induced Graft Copolymerization: Strategies and Applications

Abstract: The interest in developing antimicrobial surfaces is currently surging with the rise in global infectious disease events. Radiation-induced graft copolymerization (RIGC) is a powerful technique enabling permanent tunable and desired surface modifications imparting antimicrobial properties to polymer substrates to prevent disease transmission and provide safer biomaterials and healthcare products. This review aims to provide a broader perspective of the progress taking place in strategies for designing various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 186 publications
(248 reference statements)
0
18
0
Order By: Relevance
“…Although, the water drop contact angle showed that the surface of the PP-g-MMA was wet consistently as the contact angle decreased while the grafting degree increased. Overall, the swelling and contact angle results suggest an increase in the surface energy of the grafted films, being that suitable to use in drug release systems [34].…”
Section: Discussionmentioning
confidence: 87%
“…Although, the water drop contact angle showed that the surface of the PP-g-MMA was wet consistently as the contact angle decreased while the grafting degree increased. Overall, the swelling and contact angle results suggest an increase in the surface energy of the grafted films, being that suitable to use in drug release systems [34].…”
Section: Discussionmentioning
confidence: 87%
“…The water drop contact angle showed that the surface of the PP- g -MMA was wet consistently as the contact angle decreased while the grafting degree increased. Overall, the swelling and contact angle results suggest an increase in the surface energy of the grafted films and are suitable to use in drug release systems [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…After 24 hours . Centrifugation the solution at 15000 rpm for 15 min, and then filtering by use filter paper (20) . Pour the solution into a dish and let it .…”
Section: Preparation Of Silver Nanoparticlesmentioning
confidence: 99%